analysis of the lidia breed current situation. Conservation of the encastes in danger of extinction - Lomillos, JM.; Alonso de la Varga, ME. (Revista Complutense de Ciencias Veterinarias, 2017)
The lidia breed dates back to the Middle Ages in our country and it is constituted by 5 castas, 16 encastes and 6 genetic lines. In recent years, the lidia cattle has been reduced due to the economic crisis, which has led many farmers to reduce or replace their animals for more profitable breeds. Despite the fact that the breed is not considered endangered by MAGRAMA, a census carried out in 2010 yielded alarming data: 16 encastes in danger of extinction (with less than 1000 cows each). The demonstrated genetic importance of lidia cattle requires a greater coordination between the organisms and entities involved in their exploitation and, at the same time, the establishment of a center for lidia breed study and conservation, with a germplasm bank with a enough volume of genetic material to ensure their survival.
Keywords: Lidia cattle; livestock; bovine; bull; encaste; extinction